Peran Audit Forensik dalam Pembuktian Manipulasi Laporan Keuangan di Indonesia: Analisis Periode 2020–2025 - Aryanto Nur; Suhada . (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
Financial statement manipulation in Indonesia during 2020–2025 has increased in modus complexity, threatening the integrity of the national financial system. This study aims to analyze the role of forensic audit in proving financial statement manipulation and to evaluate its effectiveness in detecting, uncovering, and providing legally admissible evidence of fraudulent financial reporting practices during 2020–2025. The research employs a qualitative method with a multiple case study design on five entities: PT Garuda Indonesia, PT Pupuk Indonesia, PT Taspen, PT Telkom Indonesia, and PT Duta Palma. Data were collected through analysis of 26 Audit Reports of the Supreme Audit Agency (2020–2025), investigation reports of the Corruption Eradication Commission (2024–2025), findings of the Financial Transaction Reports and Analysis Center (2025–2026), and a systematic literature review. Data analysis used the Fraud Triangle, Fraud Hexagon, and Digital Forensics frameworks. The results show that forensic audit effectively uncovers five manipulation modes with a detection rate of up to 85%. The Garuda Indonesia case (2025) revealed IDR 8.2 trillion manipulation through Benford's Law. PPATK findings (2026) identified IDR 12.49 trillion revenue concealment in the textile sector. Only 34% of cases successfully reached court due to limited evidence meeting legal standards. Conclusion: forensic audit plays a critical role in early detection, in-depth investigation, and provision of legal evidence. Challenges include limited certified auditors (450 nationally), no mandatory requirement for state-owned enterprises, and weak whistleblower protection. The study recommends mandatory periodic forensic audits, human resource strengthening, optimization of digital forensics, and regulatory revision.